2020
DOI: 10.1097/md.0000000000019515
|View full text |Cite
|
Sign up to set email alerts
|

A CARE-compliant article: Unicentric Castleman disease presenting as a retroperitoneal mass of the upper edge of the pancreas

Abstract: Rationale: Castleman disease (CD) is a rare lymphoproliferative disease with a poorly understood etiology. The occurrence of CD in the abdominal cavity is very rare, especially in the retroperitoneal peripancreatic region. Patient concerns: A 33-year-old woman was referred to our department on March 1, 2018 for a detailed physical examination due to retroperitoneal peripancreatic lymph node enlargement over 15 days. Diagnosis: Enhanced magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…3 The antegrade urography of the left (A) and right (B) kidney, and contrast-enhanced abdominal CT urography of the lesions (red arrow) during plain scan phase (C), arterial phase (D), venous phase (E) and delayed phase (F) in case 2 kidney malignancy by imaging alone. Furthermore, the postoperative histopathological result of CD is generally different from the preoperative imaging diagnosis [30]. Unfortunately, core needle biopsy was not taken to confirm the preoperative pathological diagnosis, resulting in subsequent radical nephrectomy in case 1.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…3 The antegrade urography of the left (A) and right (B) kidney, and contrast-enhanced abdominal CT urography of the lesions (red arrow) during plain scan phase (C), arterial phase (D), venous phase (E) and delayed phase (F) in case 2 kidney malignancy by imaging alone. Furthermore, the postoperative histopathological result of CD is generally different from the preoperative imaging diagnosis [30]. Unfortunately, core needle biopsy was not taken to confirm the preoperative pathological diagnosis, resulting in subsequent radical nephrectomy in case 1.…”
Section: Discussionmentioning
confidence: 96%
“…Due to the lack of specificity in imaging findings, it is difficult to distinguish them from kidney malignancy by imaging alone. Furthermore, the postoperative histopathological result of CD is generally different from the preoperative imaging diagnosis [ 30 ]. Unfortunately, core needle biopsy was not taken to confirm the preoperative pathological diagnosis, resulting in subsequent radical nephrectomy in case 1.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of speci city in imaging ndings, it is di cult to distinguish them from kidney malignancy by imaging alone. Furthermore, the postoperative histopathological result of CD is generally different from the preoperative imaging diagnosis (27).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, reactive lymph node involvement is frequently observed in a rare CD subvariant of TAFRO (thrombocytopenia, ascites/anasarca, myelofibrosis/fever, renal dysfunction/reticulin fibrosis, and organomegaly) [ 28 ]. A few studies have found unicentric HV-CD arising from an accessory spleen or reported Castleman tumors arising from other uncommon locations [ 29 33 ]. However, our case strongly favors the tumor arising from a lymph node.…”
Section: Discussionmentioning
confidence: 99%